2019
DOI: 10.1177/0885328219888841
|View full text |Cite
|
Sign up to set email alerts
|

Polydioxanone implants: A systematic review on safety and performance in patients

Abstract: Background Medical devices made of polydioxanone (a synthetic biodegradable polymer) have been available since the early 1980s. However, no review regarding their performance and safety has been published. Objective This systematic review intends to review and assess commercially available polydioxanone implants and their safety and performance in patients. Methods We searched for approved polydioxanone implants in several Food and Drug Administration databases. Then, we performed a literature search for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 57 publications
0
54
0
Order By: Relevance
“…This reduces the molecular weight but not the mass. Short crystalline polymer chains are hydrolized and in a last step the remaining polymer chains are removed by the surrounding medium which leads to loss of polymer mass, molecular weight and physical properties [6,7]. Regarding the molecular weight loss (Figure 2), PDO shows the major changes in the first week resulting in a value of 38% (see table 1) caused by the hydrolysis of amorphous PDO regions, enhanced by temperature and elevated pH.…”
Section: Resultsmentioning
confidence: 99%
“…This reduces the molecular weight but not the mass. Short crystalline polymer chains are hydrolized and in a last step the remaining polymer chains are removed by the surrounding medium which leads to loss of polymer mass, molecular weight and physical properties [6,7]. Regarding the molecular weight loss (Figure 2), PDO shows the major changes in the first week resulting in a value of 38% (see table 1) caused by the hydrolysis of amorphous PDO regions, enhanced by temperature and elevated pH.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that PPDO implants are able to maintain mechanical integrity in three months and absorbed entirely in 6 months in aqueous environment [ 50 ]. In addition, PPDO implant has been certified by FDA [ 51 ], which shows good biocompatibility in vivo in many studies [ 37 , 52 , 53 ]. Thus, the BRS fabricated by PPDO material can maintain lumen open during vascular healing process with acceptable biocompatibility and suitable degradation time, which is beneficial for patients with congenital heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…An easily applied resorbable device designed as a self‐locking loop for larger vessels or vascular tissue could be a valuable surgical aid, especially when performing standing castrations in horses. Simultaneously with the reorganization of the vascular tissue, the device would ideally be hydrolyzed into low molecular weight products or metabolized, [ 4 ] which will finally lead to complete absorption of the device with a minor immunological response. A commonly used monofilament suture material is polydioxanone (PDO), a flexible, biodegradable, and biocompatible polymer.…”
Section: Introductionmentioning
confidence: 99%